2021
DOI: 10.1109/tse.2019.2903039
|View full text |Cite
|
Sign up to set email alerts
|

Understanding How and Why Developers Seek and Analyze API-Related Opinions

Abstract: With the advent and proliferation of online developer forums as informal documentation, developers often share their opinions about the APIs they use. Thus, opinions of others often shape the developer's perception and decisions related to software development. For example, the choice of an API or how to reuse the functionality the API offers are, to a considerable degree, conditioned upon what other developers think about the API. While many developers refer to and rely on such opinion-rich information about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 87 publications
(241 reference statements)
3
28
0
Order By: Relevance
“…Such a problem definition adds contextual information over the question title, which may not be enough to explain properly the development task. This assumption is consistent with our previous findings of surveys of software developers who reported the necessity of adding contextual and situationally relevant information into summaries produced from developer forums [89].…”
Section: Work Related To the Three Proposed Algorithmssupporting
confidence: 92%
See 1 more Smart Citation
“…Such a problem definition adds contextual information over the question title, which may not be enough to explain properly the development task. This assumption is consistent with our previous findings of surveys of software developers who reported the necessity of adding contextual and situationally relevant information into summaries produced from developer forums [89].…”
Section: Work Related To the Three Proposed Algorithmssupporting
confidence: 92%
“…In our previous research of two surveys We also found that developers use such documentation to support diverse development tasks (e.g., bug fixing, API selection, feature usage, etc.) [88]. Therefore, it is necessary that our mining framework is capable of supporting any development scenario.…”
Section: What Is the Performance Of The Algorithm To Link Code Examplmentioning
confidence: 99%
“…Stack Overflow is a popular software question and answer platform with extensive discussion on APIs as well as a rich amount of API reviews [2]. It becomes a valuable resource and attracts many researchers to further leverage the API information for developers [1], [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research found that API documentation often suffers from quality problems, i.e., incomplete, obsolete, and/or incorrect API documentation [4]. Thus, many developers seek help and insights about API from other developers in online developer forums (i.e., Stack Overflow) [2]. Uddin et al [2] surveyed 178 software developers to understand their requirements when searching for API information on Q&A platforms.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not always clear how to compare and select the best library from a seemingly similar set of available libraries. Thus, developers often spend time to understand differences between available libraries by, for example, reading the libraries' documentation or searching for blogs or posts on Stack Overflow [17,22]. To save developers' time and address their need to compare libraries, we previously proposed the idea of metric-based library comparisons [7,8] where we compiled a set of metrics that can be used to compare libraries.…”
mentioning
confidence: 99%